Find 4 × 9 1 + 9 × 1 4 1 + 1 4 × 1 9 1 +...+ 1 9 9 9 × 2 0 0 4 1
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Another solution:
4 × 9 1 + 9 × 1 4 1 = 4 × 9 × 1 4 1 4 + 4 × 9 × 1 4 4 = 4 × 9 × 1 4 1 8 = 4 × 1 4 2
Next, we add the third term:
4 × 1 4 2 + 1 4 × 1 9 1 = 4 × 1 4 × 1 9 3 8 + 4 × 1 4 × 1 9 4 = 4 × 1 4 × 1 9 4 2 = 4 × 1 9 3
Have you noticed a pattern? If yes, good for you. The sum of the expression
4 × 9 1 + 9 × 1 4 1 + 1 4 × 1 9 1 + … + ( 5 n − 1 ) ( 5 n + 4 ) 1
where n is the number of terms in the expression, is equivalent to
4 × ( 5 n + 4 ) n
Now, for this particular sum, the total is given as
4 × 2 0 0 4 n
We need to find the value of n :
2 0 0 4 = 5 n + 4 5 n = 2 0 0 0 n = 4 0 0
Substitute it in:
4 × 2 0 0 4 4 0 0 = 2 0 0 4 1 0 0 = 5 0 1 2 5
Therefore,
4 × 9 1 + 9 × 1 4 1 + 1 4 × 1 9 1 + … + 1 9 9 9 × 2 0 0 4 1 = 5 0 1 2 5
Problem Loading...
Note Loading...
Set Loading...
let 4 × 9 1 = n ( n + 5 ) 1
n ( n + 5 ) 1 = n A + n + 5 B
1=A(n+5)+B(n)
Substituting n=0 and n=-5 gives us A= 5 1 and B=- 5 1
Substituting A and B back will give us 5 n 1 - 5 n + 2 5 1
Now the expression becomes
4 × 9 1 + 9 × 1 4 1 + 7 0 1 - 9 5 1 + 9 5 1 - 1 2 0 1 + 1 2 0 1 - 1 4 5 1 +...+ 9 9 7 0 1 - 9 9 9 5 1 + 9 9 9 5 1 - 1 0 0 2 0 1
where the center part telescopes and what's left would be
2 0 1 - 1 0 0 2 0 1 = 5 0 1 2 5